China, Asia, and the new world economy - Eichengreen, Barry J.; Wyplosz, Charles; d (Oxford : Oxford University Press, 2008)
This timely collection of 15 essays by leading economists explores how rapid economic growth in China and elsewhere in East Asia is reshaping the world economy.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Finance -- China; International economic relations; China -- Economic conditions -- 2000-; China -- Foreign economic relations; China -- Economic policy; East Asia -- Economic conditions -- 1945-; East Asia -- Foreign economic relations